Respuesta :

Answer:

[tex](-13) * (-13) = (-13)^{2}[/tex]

[tex]35 * 35 = 35^{2}[/tex]

Step-by-step explanation:

Given

[tex](-13) * (-13)[/tex]

Required

Express as an exponential notation

[tex](-13) * (-13)[/tex]

Apply the following law of indices

[tex]x^a * x^b = x^{a+b}[/tex]

This gives:

[tex](-13) * (-13) = (-13)^{1+1}[/tex]

[tex](-13) * (-13) = (-13)^{2}[/tex]

The second complete is incomplete; However, I'll assume it is: 35 times 35

[tex]35 * 35[/tex]

Using the same law applied in (1) above:

[tex]35 * 35 = 35^{1+1}[/tex]

[tex]35 * 35 = 35^{2}[/tex]